ANALYSIS OF THE INFLUENCE OF MARKETING COMMUNICATIONS ON LOCAL SKIN CARE ANTI-AGING AWARENESS: CRYSTALLURE IN MEDAN CITY - Zharifah Putri Masturah Hasibuan; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2023)
The most common facial skin problems experienced by Indonesian women are dull skin conditions and the appearance of wrinkles and fine lines which are signs of premature aging. This problem can be overcome by using anti-aging skin care. One of the local anti-aging skin care brands in Indonesia is Crystallure, which is produced by PT Paragon Technology and Innovation. It is important for companies to implement traditional and digital marketing strategies simultaneously in order to increase brand awareness. The marketing communications used by Crystallure to promote its brand are social media marketing, sales promotions, exhibitions, personal selling, and word-of-mouth. The type of research used is descriptive causal with a quantitative approach. The sampling technique used in this study was non-probability sampling, namely purposive sampling. The number of samples used in this study were 91 samples. This study used multiple linear regression analysis using SPSS version 25. The results showed that exhibitions, personal selling, and word-of-mouth partially had a significant effect on brand awareness. Meanwhile, social media marketing and sales promotion partially have no significant effect on brand awareness. And social media marketing, sales promotions, exhibitions, personal selling, and word-of-mouth all influence brand awareness. and word-of-mouth partially has a significant effect on brand awareness. Meanwhile, social media marketing and sales promotion partially have no significant effect on brand awareness. And social media marketing, sales promotions, exhibitions, personal selling, and word-of-mouth all influence brand awareness. and word-of-mouth partially has a significant effect on brand awareness. Meanwhile, social media marketing and sales promotion partially have no significant effect on brand awareness. And social media marketing, sales promotions, exhibitions, personal selling, and word-of-mouth all influence brand awareness.